Two samples for blood transfusion: single centre experience. Issue 4 (30th April 2014) - Thomas, W.; Davies, J.; Asamoah, A.; Scott‐Molloy, C.; Sansom, V.; Kerr, J.
SUMMARY Objectives The aim of this study was to evaluate the introduction of two‐sample policy for transfusion at our hospital and reduction of the risk of ABO incompatible transfusion. Background ABO incompatible transfusion can be a fatal but avoidable event. Wrong blood in tube is a cause of ABO incompatible transfusion and there are various strategies available to try and expunge this event. Methods Survey of policy/practice before and after the introduction of a two‐sample policy. Results Staff training is inadequate in reducing the risk of ABO incompatible transfusion. A two‐sample policy was introduced and does not significantly increase workload or use of group O blood and does not compromise patient safety by causing delay in blood provision. Post hoc analysis confirms good understanding of the policy by medical staff. Observation of medical staff taking transfusion samples demonstrated consistent deviation from policy, enforcing the need for confirmatory samples. Conclusion A two‐sample policy adds an extra layer of safety to transfusion practice and can be introduced without creating new problems.